Misuse Versus Underuse: A Socio-Legal analysis of Women Protection Laws in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The discourse surrounding women protection laws in India has evolved from a focus on affirmative protection to debates over alleged misuse and underuse. While legislative efforts since the 1980s have aimed at safeguarding women against domestic violence, sexual harassment, and dowry-related offenses, public narratives increasingly question the implementation, fairness, and societal impact of these statutes. This article undertakes a socio-legal analysis of the competing claims of misuse and underuse of women protection laws in India, exploring legal frameworks, judicial attitudes, data trends, and socio-cultural realities. The research contends that both misuse and underuse co-exist due to systemic gaps in enforcement, lack of gender-sensitive adjudication, and social stigma that deters reporting. International comparisons reveal parallel challenges in balancing women’s protection with procedural fairness. The article concludes by arguing for nuanced reforms grounded in empirical evidence, judicial guidance, and social education, while foreseeing future research avenues in gender justice.